Method for manufacturing fibrous cellulose composite resin
Patent Information
- Application Number
- JP2025059282
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
Smart Images

Figure 2026166390000001_ABST
Abstract
Description
[Technical Field]
[0001] This invention relates to a method for producing fibrous cellulose composite resins. [Background technology]
[0002] In recent years, fine cellulose fibers such as cellulose nanofibers and microfiber cellulose (microfibrillated cellulose) have attracted attention for their use as reinforcing materials in resins, and many proposals have been made.
[0003] To obtain this type of composite resin, a material containing resin and fine fibrous cellulose (hereinafter also simply referred to as "fibrous cellulose") is melted and kneaded with the resin using a melt-kneading extruder to produce the composite resin.
[0004] In Patent Document 1, the applicant disclosed a fibrous cellulose-containing material and a fibrous cellulose composite resin containing this fibrous cellulose-containing material. [Prior art documents] [Patent Documents]
[0005] [Patent Document 1] Patent No. 7557494 [Patent Document 2] Japanese Patent Publication No. 2024-107247 [Overview of the project] [Problems that the invention aims to solve]
[0006] Patent Document 1 discloses, as an example, the drying of a fibrous cellulose-containing material using a drum dryer commonly used for drying paper, and the detailed description of the invention discloses the possibility of dehydrating the fibrous cellulose-containing material prior to drying.
[0007] However, we found that drum dryers consume too much energy, and under certain conditions, the drying material can stick to the drum surface, leading to operational problems.
[0008] Therefore, the main objective of the present invention is to provide a method for producing fibrous cellulose composite resin that can significantly reduce the energy required for drying. [Means for solving the problem]
[0009] The embodiments of the present invention for solving the above technical problems are as follows. (First aspect) A dehydration step is performed in which an aqueous dispersion containing fibrous cellulose at a solid content concentration of 2 to 10% by mass is dehydrated to a solid content concentration of 20 to 80% by mass using a filter press or screw press. A drying process in which the dehydrated material is dried to a moisture content of 10% or less using an indirect heating type steam tube dryer, A composite resin formation process involves kneading the dried material after a drying process to obtain a composite resin, The process includes a resin-containing step in which a resin is added prior to the composite resin formation step. A method for producing a composite resin characterized by the above. [Effects of the Invention]
[0010] According to the present invention, it is possible to provide a method for producing fibrous cellulose composite resin that can significantly reduce the energy required for drying. [Brief explanation of the drawing]
[0011] [Figure 1] This is a flow sheet illustrating a series of composite resin manufacturing examples. [Figure 2] This shows the results of the dispersion test. [Figure 3] This shows the results of dispersibility tests under different drying equipment. [Figure 4] The above image shows a microscopic photograph. MODE FOR CARRYING OUT THE INVENTION
[0012] Hereinafter, preferred embodiments of the present invention will be described. The content of the present invention should be interpreted based on the matters recited in the claims, and should not be interpreted as being limited to the embodiments.
[0013] (Summary of the Embodiments of the Present Invention) The present invention aims to obtain a composite resin made of a material containing a resin and fibrous cellulose.
[0014] As disclosed in Patent Document 1, it is desirable to dry the fibrous cellulose-containing material. From this viewpoint, the present applicant has studied drying using a drum dryer that is widely used for drying paper, including actual equipment tests. As a drum dryer based on the thin-film drying method, the present applicant disclosed in Patent Document 2 that "John Milder Model JM-T" manufactured by Johnson Boiler Co., Ltd. is used.
[0015] In addition, Patent Document 2 includes the following disclosure. That is, fibrous cellulose can be supplied to a drum dryer that performs drying treatment in a state of, for example, a slurry (aqueous dispersion), and in this case, drying is performed at a fine fibrous cellulose content (absolute dry mass%) of 1 mass% or more and 10 mass% or less. In the drum dryer, a mild drying treatment is performed, and a dried product having a relatively small specific surface area is obtained. The drying treatment can be carried out under normal pressure. The surface temperature of the inner surface of the drum is 80 to 200°C, and the rotational speed of the drum dryer may be, for example, 0.5 rpm or more and 2 rpm or less, although it depends on the inner diameter of the drum and the input amount of the slurry. The time for drying with the drum dryer depends on the input amount of the slurry, but 1 to 60 seconds is sufficient for complete drying, and even if the drying is performed for a time longer than that, the moisture content of the dried product will not decrease any further.
[0016] However, this method involves supplying fibrous cellulose to a drum dryer with a fibrous cellulose content (oven-dry mass%) of 1% to 10% or less, maintaining a surface temperature of 80-200°C on the inside of the drum, and obtaining a dried product in 1-60 seconds, which requires a large amount of thermal energy. In particular, while it may be possible to somehow include the cost of thermal energy in the product price for small-scale production, when considering large-scale production, the cost of thermal energy becomes a bottleneck, posing a fundamental problem that prevents a reduction in product prices.
[0017] Therefore, in the embodiments of the present invention, instead of directly obtaining a dried product from a fibrous cellulose-containing material, a dried product is obtained by undergoing dehydration and drying treatments.
[0018] In other words, a dehydration step is performed in which an aqueous dispersion containing fibrous cellulose at a solid content concentration of 2 to 10% by mass is dehydrated to a solid content concentration of 20 to 80% by mass using a filter press or screw press. A drying process in which the dehydrated material is dried to a moisture content of 10% or less using an indirect heating type steam tube dryer, A composite resin formation process involves kneading the dried material after a drying process to obtain a composite resin, The process includes a resin-containing step in which a resin is added prior to the composite resin formation step.
[0019] The reason for using an aqueous dispersion containing fibrous cellulose at a solid content concentration of 2-10% by mass is that an aqueous dispersion with less than 2% by mass requires a great deal of energy for dehydration and subsequent drying. Furthermore, when fibrous cellulose is used as an aqueous dispersion with a solid content concentration exceeding 10% by mass, there is a risk that its kneadability with resins or materials containing resins will decrease.
[0020] To illustrate with an example, the embodiment of Patent Document 2 and the embodiment of the present invention are as follows. The embodiment described in Patent Document 2 involves directly drying an aqueous dispersion of fibrous cellulose with a moisture content of 96% to obtain a dry product with a moisture content of 10%. In this embodiment of Patent Document 2, if the oven-dry weight is 1 kg, it is necessary to dry approximately 24 kg of water to obtain a dry product with a moisture content of 10%. In contrast, the present invention involves dehydrating an aqueous dispersion of fibrous cellulose with a moisture content of 96% to a dehydrated portion with a moisture content of 50%, and then drying it to a dry product with a moisture content of 10%. In this embodiment of the present invention, if the oven-dry weight is 1 kg, it is sufficient to dry approximately 1 kg of water to obtain a dry product with a moisture content of 10%.
[0021] On the other hand, aqueous dispersions of fibrous cellulose tend to aggregate irreversibly during the drying process, and as a result, these aggregates remain when compounded with resin.
[0022] Therefore, for example, by using a resin mixing process, the resin (component) can be pre-mixed into the aqueous dispersion of fibrous cellulose, and then drying can prevent aggregation during the drying process of the aqueous dispersion of fibrous cellulose.
[0023] In this case, the aforementioned resin (component) can be an acid-modified resin, as described later. When this acid-modified resin is used in carbamate-treated fibrous cellulose, some or all of the carbamate groups ionically bond with the acid groups of the acid-modified resin. This ionic bonding improves the reinforcing effect of the resin. Maleic anhydride-modified polypropylene is preferred as the acid-modified resin.
[0024] From this perspective, prior to supplying the aqueous dispersion of fibrous cellulose to the screw press, that is, prior to the dehydration step, it is preferable to include, for example, a powdered resin (e.g., polypropylene resin) in a "resin mixing step" to improve the dispersibility of the fibrous cellulose in the resin. In the stage including this "resin mixing process," an acid-modified resin and / or a dispersant may be included. The acid-modified resin and / or dispersant enhance the dispersibility of fibrous cellulose in the resin. As the acid-modified resin, for example, a maleic anhydride-modified polypropylene resin can be used for mixing. A "fibrous cellulose-containing material" impregnated with resin can be obtained through the "resin mixing process." The appropriate amount of resin to mix will be described later.
[0025] It is desirable to have a crushing step between the dewatering step and the drying step in which the dewatered material is crushed. Since the size and shape of the dewatered material are too uneven, the drying efficiency is improved by equalizing the size and shape.
[0026] In the "composite resin formation process," if the dried material, after going through the drying process, is kneaded, for example, using a kneading and extrusion machine to obtain a composite resin, the dispersibility of fibrous cellulose in the resin becomes good. If necessary, as shown in Figure 1, a portion of the target resin can be mixed in advance in the aforementioned "resin mixing process," and then, for example, the remaining amount of the target resin can be added in a kneading and extrusion machine to disperse the fibrous cellulose in the resin. In this configuration, the "resin mixing process" and the "kneading process" which involves adding the remaining amount of the target resin constitute the "resin-containing process." As can be seen from this explanation, it is sufficient for the resin to be incorporated before or during the "mixing process" or "composite resin formation process," and there are no restrictions on at which stage the resin is incorporated.
[0027] In the composite resin formation process, it is desirable to further include a product formation process in which, for example, the composite resin obtained by kneading in a kneading and extruding machine is extruded as strands, the extruded material is cut into length units, and the cut pieces are dewatered to obtain a composite resin in the form of pellets. The pelletized composite resin offers good handling properties when the user subsequently performs processing such as injection molding.
[0028] (Example of the overall manufacturing flow) Figure 1 shows an example of the overall manufacturing flow. It is clear that the flow parts other than the processes defined in this invention are not essential to this invention.
[0029] (Dehydration process) As the equipment used for dewatering, it is possible to select and use one or more types from among dewatering equipment such as belt presses, screw presses, filter presses, twin rolls, twin wire formers, valveless filters, center disc filters, membrane processing equipment, and centrifuges.
[0030] Prior to completing the present invention, the inventors performed dehydration using a centrifuge, but the dehydration concentration was only about 23%, which was not entirely satisfactory, compared to the target dehydration concentration of 20% or more.
[0031] In the case of filter presses, when dewatering was performed using two commercially available filter press models, the dewatered cake concentration was 52-53%, and the filtrate concentration was approximately 40 ppm, resulting in a high yield. However, a drawback was found: the dehydrated cake was hard, making transportation and crushing difficult.
[0032] On the other hand, in the process of exploring the possibility of employing other dewatering methods, an experiment was conducted in which dewatering was performed in the first stage using a rotary screen and in the second stage using a screw press. As a result, the dewatering concentration with the rotary screen in the first stage was only about 6.7%, which was insufficient. It was considered that the significance of dewatering in the first stage was almost nonexistent. Therefore, we considered whether dewatering could be achieved using only a screw press, and after trial and error, we investigated the size of the filtration pores in the filtration screen inlet, low-pressure zone, and high-pressure zone, as well as the screw rotation speed, and found that the dewatered cake concentration exceeded 56%.
[0033] It was found that dewatered cake produced by a screw press is easily crushed, which has the advantage of being easy to handle and to dismantle.
[0034] (Crushing / drying process) Mixer dryer The dewatered cakes, obtained by dewatering with a filter press and a screw press, were crushed using a continuous crushing blade screw feeder, and then dried using a mixer dryer. The test results showed that, for both filter-pressed and screw-pressed dehydrated cakes, a powder with a moisture content of approximately 1-3% could be obtained by drying. However, the difference between filter-pressed and screw-pressed dehydrated cakes is that the filter-pressed cakes have a higher moisture content of 3% compared to the screw-pressed cakes (the latter being about 1%), and tend to have a lower processing volume. From this perspective, drying in a mixer dryer was more suitable for screw-pressed dehydrated cakes.
[0035] However, drying with a mixer dryer (dryer temperature 152°C) resulted in several issues: the raw material adhering to the inner wall of the dryer, the dried powder moisture content being over-dried at approximately 1% compared to the target of 5%, and the dried powder temperature reaching nearly 100°C. To address this phenomenon, we found that by lowering the dryer temperature (for example, to 120°C) and adjusting the rotation speed of the stirring paddle, the raw material does not adhere to the inner wall of the dryer, the moisture content of the dried powder becomes about 7%, and the temperature of the dried powder becomes about 50°C.
[0036] • Disc dryer The dehydrated cake, which had been dehydrated using a filter press, was crushed into pieces approximately 10 cm square, and a drying test was conducted using a disc dryer. The test results showed that the dewatered cake was not sufficiently crushed in the disc dryer, resulting in a dry, powdery material with larger particles and clumps of about 30 mm in size (which were not completely dry inside). The moisture content of the dry powder after removing the 30 mm clumps was 8.2%. The dewatered cake from the filter press, which had been pre-mixed with resin, was less prone to crumbling compared to typical dewatered cakes made from sludge, etc. However, the agitation effect of the disc dryer did not allow the inside to dry completely, leaving lumps behind, and the entire dried product could not be dried to the target moisture content (10% or less).
[0037] • Steam tube dryer The dehydrated cakes, obtained by dewatering with a filter press and a screw press, were crushed using two types of crushers: a continuous paddle mixer and a batch mixer, and then dried using a tube dryer test machine. Test results showed that the continuous paddle mixer was unable to crush the material, but the batch mixer was able to.
[0038] Therefore, the material crushed using a batch mixer was dried using a tube dryer. As a result, both the filter-pressed and screw-pressed products yielded dry powder with a moisture content of approximately 4%. The results are shown in [Table 1]. Regarding the difference between dewatered cake produced using a filter press and a screw press, the filter press product had a longer crushing time and larger crushed particle size, but there was no significant difference in drying efficiency.
[0039] [Table 1]
[0040] On the other hand, two issues were identified: issue 1 was the presence of lumps of about 20 mm in size in the dried powder (there were more lumps in the filter-pressed product), and issue 2 was that the powder temperature after drying reached nearly 100°C.
[0041] Regarding problem l (the presence of lumps of about 20 mm in the dry powder): It was confirmed that the lumps of about 20 mm in size within the powder were dry inside, and that there was no difference in composition between the lumps and the powder. Therefore, we concluded that the problem could be solved by two methods of equipment-based countermeasures: firstly, by preventing the formation of lumps during crushing before drying, and secondly, by removing the lumps after drying or by re-crushing the lumps.
[0042] When continuous operation is performed with lumps of about 20 mm remaining after drying, it is necessary to select an optimal crusher to ensure that the lumps do not become under-dried and that there is no imbalance in the composition between the powder and the lumps. A continuous hammer-type crusher, also used for crushing dewatered cake from filter presses, was selected and compared with a batch-type mixer in a comparative test. The results are shown in [Table 2]. The test results showed that with batch mixers, extending the processing time reduced the amount of clumping, while with continuous hammer crushers, setting a higher rotation speed eliminated the clumps.
[0043] [Table 2]
[0044] Regarding Problem 2 (The powder temperature after drying reaches nearly 100°C): Lowering the temperature of the dried powder after drying (targeting around 50-60°C) can be achieved by sieving the dried product or by exchanging heat with air during the airflow process.
[0045] Based on the above considerations, a comparative study was conducted between the energy consumption required to perform drying with the aforementioned drum dryer and the energy consumption required to perform the process including the dewatering and drying steps according to the present invention. The results are shown in [Table 3]. As these results show, the energy consumption for carrying out a process including dehydration and drying is significantly lower than the energy consumption for drying with a drum dryer, making it a useful process.
[0046] [Table 3]
[0047] On the other hand, when fibrous cellulose and resin (polypropylene maleate anhydride) were kneaded together to form a composite resin, the quality of the composite resin (particularly dispersibility and strength) was compared between a process including a dehydration step and a drying step, and a process drying with a drum dryer. In comparing the quality of composite resins, the compound was diluted to 10% with polypropylene, and its flexural modulus, flexural strength, and dispersibility after being formed into a hot-pressed sheet were examined. The results are shown in [Table 4].
[0048] [Table 4]
[0049] Although there is no significant difference in flexural modulus and flexural strength, visual inspection of the dispersibility after forming a hot-pressed sheet reveals that, as shown in Figure 2, there are many aggregates when using a drum dryer drying process.
[0050] In the dewatering process, dewatering is carried out so that the solid content concentration is 20% by mass or more, preferably 30% by mass or more, and more preferably 43% by mass or more. By carrying out dewatering in the dewatering process so that the solid content concentration is 20% by mass or more, the energy efficiency of the entire manufacturing process can be increased, and the likelihood of equipment contamination can be reduced, thereby improving operability. Furthermore, the dewatering in the dewatering process is carried out so that the solid content concentration is 80% by mass or less, preferably 70% by mass or less, and more preferably 65% by mass or less. By carrying out the dewatering in the dewatering process so that the solid content concentration is 80% by mass or less, operation can be carried out without reaching the dewatering limit, improving energy efficiency, and enabling efficient crushing and other processes in subsequent steps.
[0051] Based on the above findings, we concluded that a process including dehydration and drying steps is suitable. (Optimal dehydration equipment) It was found that filter presses and screw presses are suitable as dewatering equipment. However, while filter presses have the advantages of low filtrate concentration and high dewatering yield, they have drawbacks such as the need to replace the filter cloth (replacement of consumables), requiring batch operation and not being able to operate continuously, and the dewatered cake being hard, making it difficult to transport and crush. In contrast, screw presses have the advantage of relatively high filtrate concentration and a large amount of cellulose fiber circulation within the system, requiring countermeasures, but they do not require replacement of consumables, can be operated continuously, and the dewatered cake is easily broken down, with good transportability and crushing properties. Considering these advantages and disadvantages, while a filter press is also a viable option, a screw press is preferable.
[0052] (Optimal drying equipment) It was found that mixer dryers and steam tube dryers are suitable drying equipment. In order to find the optimal drying equipment, we attempted the following:
[0053] We changed the raw material cellulose fiber from unmodified cellulose fiber to carbamate-modified cellulose fiber, and changed the polypropylene maleate anhydride (MAPP) from MAPP produced by the wet method to MAPP produced by the cheaper dry method. We conducted tests to evaluate the dewatering and drying equipment and to resolve any issues. In tests using a dewatering machine (screw press), the particle size of wet-process MAPP increased from approximately 20 μm to approximately 400 μm for dry-process MAPP, improving water extraction. Additionally, the hydrophobicity of the fibers due to carbamate modification increased the processing capacity from approximately 25 kg / hr to approximately 57 kg / hr.
[0054] As previously mentioned, in mixer dryers, a phenomenon is observed where the raw materials adhere to the dryer at a temperature of 152°C. Therefore, it was found that lowering the dryer temperature to, for example, 144°C could prevent the raw materials from sticking to the mixer dryer, but the processing rate decreased from approximately 43 kg / hr to approximately 30 kg / hr.
[0055] The dispersibility of aggregates during drying using a mixer dryer was investigated. A mixer dryer is based on the principle of drying raw materials by pushing them forward and pressing them against the casing with blades that rotate at high speed inside a cylindrical casing heated by steam. Prior to drying, the raw materials were crushed using a hammer-type mixer, which offers excellent crushing properties. We investigated the factors affecting dispersibility by changing the processing conditions of the mixer dryer (blade pattern, blade rotation speed, drying temperature, and processing volume).
[0056] As a result, there was no correlation between the processing conditions and variance, and no conditions were found that improved variance. It is believed that in mixer dryers, the fibers twist when the high-speed rotating blades press the raw materials against the casing, causing aggregates to form and reducing dispersibility. Furthermore, although the test used raw materials crushed with a hammer-type mixer, it was found that excessive crushing had a counterproductive effect on drying efficiency and operability, as it improved transportability, shortened residence time, decreased drying efficiency, and increased adhesion to the blades.
[0057] (Specific considerations regarding decentralization) The raw materials, dewatered and crushed using a screw press, were completely dried in an experimental oven at 105°C. After being melt-kneaded in a twin-screw extruder to form pellets, base polypropylene was added to achieve a cellulose fiber content of 10%, and the mixture was melt-kneaded again to obtain a 10% cellulose fiber composite resin. A cellulose fiber composite resin containing 10% was processed into a sheet using a heat press, and then visually inspected. Similar evaluations were also performed on samples where the raw material after screw pressing was dried in a steam tube dryer, or in a mixer dryer. Furthermore, samples dried using a steam tube dryer or mixer dryer were not dried in a laboratory oven, but instead melted and kneaded while still containing some moisture.
[0058] The results are shown in Figure 3.
[0059] The results showed that samples dried in a mixer dryer tended to have poorer dispersibility than samples dried in a laboratory oven or steam tube dryer after screw pressing. Furthermore, no significant effect on water dispersibility was observed. Regarding the relationship between drying method and dispersibility, we focused on the state of the dried material. Microscopic observations shown in Figure 4 revealed that samples dried in an experimental oven or steam tube dryer after screw pressing resulted in granular samples. On the other hand, samples dried in a mixer dryer showed the formation of bundled fiber clumps. These bundled fiber clumps are thought to have formed as a result of the fibers becoming entangled due to friction when the raw material is pressed against the casing by the blades. Since these fiber clumps cannot be eliminated unless the fibers are cut, it is considered that dissolution of the aggregates by melt kneading is difficult, and this worsens the dispersibility.
[0060] Considering all of the above, a steam tube dryer is the most suitable drying equipment.
[0061] The following provides supplementary information regarding embodiments of the present invention. (Regarding fibrous cellulose) When obtaining a composite resin, since resins are generally hydrophobic while fibrous cellulose is hydrophilic, it is preferable to ensure good dispersibility of the fibrous cellulose when using it as a reinforcing material for the resin.
[0062] To improve dispersibility, a method of modifying fine fibrous cellulose by substituting hydroxyl groups with carbamate groups has been proposed, and its effectiveness has been demonstrated.
[0063] The fibrous cellulose composite resin in this embodiment contains fibrous cellulose and a resin, and preferably further contains an acid-modified resin. When an acid-modified resin is included, some or all of the carbamate groups are ionically bonded with the acid groups of the acid-modified resin. This ionic bonding improves the reinforcing effect of the resin.
[0064] The fibrous cellulose according to the present invention is preferably fine fiber. It is more preferably microfiber cellulose (microfibrillated cellulose) with an average fiber diameter of 0.1 μm or more. When it is microfiber cellulose, the reinforcing effect of the resin is significantly improved. Furthermore, microfiber cellulose is easier to modify with carbamate groups (carbamateization) than cellulose nanofibers, which are also fine fibers.
[0065] The microfiber cellulose according to the present invention refers to fibers with a wider average fiber width than cellulose nanofibers. Specifically, the average fiber diameter is, for example, 0.1 to 20 μm, preferably 0.2 to 19 μm, and more preferably more than 0.5 μm and 18 μm or less. If the average fiber diameter of microfiber cellulose falls below 0.1 μm, it becomes indistinguishable from cellulose nanofiber, and the effect of improving the strength (especially the flexural modulus) of the resin may not be sufficiently obtained. In addition, the defibrillation time will be longer, requiring a large amount of energy.
[0066] Furthermore, the dewatering properties of the microfiber cellulose slurry deteriorate. Poor dewatering properties require a large amount of energy for drying, and applying a large amount of energy to drying can cause thermal degradation of the microfiber cellulose, potentially reducing its strength. On the other hand, if the average fiber diameter of the microfiber cellulose exceeds 20 μm, the reinforcing effect may become insufficient.
[0067] The fibrous cellulose containing microfiber cellulose according to the present invention can be obtained by defibrating (finely pulping) a cellulose raw material (hereinafter also referred to as "raw material pulp"). As the raw material pulp, one or more types can be selected and used from, for example, wood pulp made from hardwoods, softwoods, etc., non-wood pulp made from straw, bagasse, cotton, hemp, pulp fibers, etc., recycled paper pulp (DIP) made from recycled waste paper, waste paper, etc., etc. The above-mentioned cellulose raw materials may also be in the form of crushed material (powdered material), such as cellulose powder.
[0068] However, in order to avoid the inclusion of impurities as much as possible, it is preferable to use wood pulp as the raw material pulp. As for wood pulp, one or more types can be selected and used from chemical pulps such as hardwood kraft pulp (LKP) and softwood kraft pulp (NKP), and mechanical pulp (TMP), etc.
[0069] The raw pulp can be pretreated by chemical methods prior to defibration. Examples of chemical pretreatments include hydrolysis of polysaccharides with acid (acid treatment), hydrolysis of polysaccharides with enzymes (enzyme treatment), swelling of polysaccharides with alkali (alkali treatment), oxidation of polysaccharides with an oxidizing agent (oxidation treatment), and reduction of polysaccharides with a reducing agent (reduction treatment). However, as a chemical pretreatment, enzymatic treatment is preferred, and it is more preferable to also apply one or more treatments selected from acid treatment, alkali treatment, and oxidation treatment.
[0070] For enzymatic treatment, it is preferable to use at least one of cellulase-type enzymes and hemicellulase-type enzymes, and more preferably both in combination. Using these enzymes makes defibration of cellulose raw materials easier. Cellulase-type enzymes induce the decomposition of cellulose in the presence of water. Hemicellulase-type enzymes induce the decomposition of hemicellulose in the presence of water.
[0071] The amount of enzyme added to the cellulose raw material is determined by factors such as the type of enzyme, the type of wood used as the raw material (coniferous or hardwood), and the type of mechanical pulp. However, the amount of enzyme added to the cellulose raw material is preferably 0.1 to 3% by mass, more preferably 0.3 to 2.5% by mass, and particularly preferably 0.5 to 2% by mass. If the amount of enzyme added is less than 0.1% by mass, the effect of the enzyme addition may not be sufficiently obtained. On the other hand, if the amount of enzyme added exceeds 3% by mass, the cellulose may be saccharified, and the yield of fine fibers may decrease. There is also the problem that the improvement in effect may not be commensurate with the increase in the amount of enzyme added.
[0072] When using a cellulase-type enzyme, the pH during enzyme treatment is preferably in the weakly acidic range (pH=3.0~6.9) from the viewpoint of the reactivity of the enzymatic reaction. On the other hand, when using a hemicellulase-type enzyme, the pH during enzyme treatment is preferably in the weakly alkaline range (pH=7.1~10.0).
[0073] After enzyme treatment, it is preferable to deactivate the enzyme. Methods for deactivating the enzyme include, for example, adding an alkaline aqueous solution (preferably pH 10 or higher, more preferably pH 11 or higher) or adding hot water at 80-100°C.
[0074] Enzyme treatment, acid treatment, or oxidation treatment prior to defibration can lower the water retention of fibrous cellulose, increase its crystallinity, and improve its homogeneity. In this respect, lower water retention of fibrous cellulose makes it easier to dehydrate, thus improving the dewatering properties of the fibrous cellulose slurry.
[0075] Enzymatic, acidic, or oxidative treatment of raw pulp breaks down the amorphous regions of hemicellulose and cellulose in the pulp. As a result, the energy required for defibration can be reduced, improving the uniformity and dispersibility of fibrous cellulose. However, since pretreatment reduces the aspect ratio of fibrous cellulose, it is preferable to avoid excessive pretreatment when using it as a reinforcing material for resins.
[0076] The defibration of raw pulp can be carried out by beating it using, for example, a homogenizer such as a beater, high-pressure homogenizer, or high-pressure homogenization device; a millstone-type friction machine such as a grinder or crusher; a single-screw kneader; a multi-screw kneader; a kneader refiner; or a jet mill. However, it is preferable to use a refiner or a jet mill.
[0077] The average fiber length (average length of a single fiber) of fibrous cellulose is preferably 0.10 to 2.00 mm, more preferably 0.12 to 1.50 mm, and particularly preferably 0.15 to 1.00 mm. If the average fiber length is less than 0.10 mm, a three-dimensional network of fibers cannot be formed, which may reduce the flexural modulus of the composite resin, and even if homogeneity is improved by increasing the fineness ratio to more than 35%, the reinforcing effect may not be improved. On the other hand, if the average fiber length exceeds 2.00 mm, the reinforcing effect may be insufficient. The average fiber length of fibrous cellulose can be arbitrarily adjusted, for example, by selecting raw pulp, pre-treatment, defibration, etc.
[0078] In this specification, "fine ratio" refers to the mass-based proportion of pulp fibers with a fiber length of 0.2 mm or less.
[0079] The fineness ratio of fibrous cellulose is preferably 10% or more and 55% or less, more preferably 20-50%, and particularly preferably 30-45%. When the fineness ratio is 10% or more, a certain proportion of homogeneous fibers is ensured, and the homogeneity of the composite resin is ensured. As a result, the flexural modulus is ensured. When the fine fiber content exceeds 55%, the fluidity of the composite resin decreases. This decrease in fluidity can lead to a reduction in the homogeneity of the composite resin, potentially resulting in insufficient reinforcement. In contrast, it has been found that when the fine fiber content is 55% or less, the composite resin has high fluidity, and even when the fiber content is 55% or more, it can be extruded in a strand shape using a melt-mixing extruder.
[0080] It is also preferable to keep the fineness ratio of the cellulose raw material used to make fibrous cellulose within a predetermined range. Specifically, it is preferable that the fineness ratio of the cellulose raw material used to make fibrous cellulose be 1% or more, more preferably 3-20%, and particularly preferable 5-18%. If the fineness ratio of the cellulose raw material before defibration is within the above range, it is thought that there will be less damage to the fibers after defibration, and the reinforcing effect of the resin will be improved.
[0081] The fineness ratio can be adjusted by pretreatment such as enzymatic treatment. When enzymatic treatment is performed, the fibers themselves may become brittle, potentially reducing the reinforcing effect of the resin. Therefore, from this perspective, the amount of enzyme added is preferably 2% by mass or less, more preferably 1% by mass or less, and particularly preferably 0.5% by mass or less. Alternatively, the material may be in a form without enzymatic treatment (amount added: 0% by mass).
[0082] The aspect ratio of the fibrous cellulose is preferably 2 to 15,000, more preferably 10 to 10,000. If the aspect ratio is less than 2, a three-dimensional network cannot be sufficiently constructed, and even if the average fiber length is 0.10 mm or more, the reinforcing effect may be insufficient. On the other hand, if the aspect ratio exceeds 15,000, the entanglement of the fibrous cellulose becomes high, and dispersion in the resin may be insufficient.
[0083] In this specification, "fibrillation rate" refers to the value obtained by dissociating fibrous cellulose in accordance with JIS-P-8220:2012 "Pulp - Dissociation Method" and measuring the resulting dissociated pulp using FiberLab. (Kajaani).
[0084] The fibrillation rate of fibrous cellulose is preferably 1.0 to 30.0%, more preferably 1.5 to 20.0%, and particularly preferably 2.0 to 15.0%. If the fibrillation rate exceeds 30.0%, the contact area with water becomes too large, and even if defibration is performed within the range where the average fiber width remains 0.1 μm or more, dehydration may become difficult. On the other hand, if the fibrillation rate falls below 1.0%, there are few hydrogen bonds between fibrils, and it may not be possible to form a strong three-dimensional network.
[0085] The crystallinity of the fibrous cellulose is preferably 50% or higher, more preferably 55% or higher, and particularly preferably 60% or higher. If the crystallinity falls below 50%, although the miscibility with pulp and cellulose nanofibers improves, the strength of the fibers themselves decreases, which may prevent the improvement of the resin's strength. On the other hand, the degree of crystallinity of fibrous cellulose is preferably 95% or less, more preferably 90% or less, and particularly preferably 85% or less. If the degree of crystallinity exceeds 95%, the proportion of strong hydrogen bonds within the molecule increases, the fibers themselves become rigid, and the dispersibility deteriorates. The degree of crystallinity of fibrous cellulose can be arbitrarily adjusted, for example, by selecting the raw pulp, pre-treatment, and micronization process.
[0086] As previously mentioned, it is preferable to use fibrous cellulose that has carbamate groups. There are no particular limitations on how the carbamate groups are obtained. For example, the cellulose raw material may have carbamate groups because it has been carbamateized, or the fibrous cellulose (finely ground cellulose raw material) may have carbamate groups because it has been carbamateized.
[0087] Here, "having a carbamate group" means that a carbamate group (an ester of carbamic acid) has been introduced into the fibrous cellulose. The carbamate group is a group represented by -O-CO-NH-, such as -O-CO-NH2, -O-CONHR, -O-CO-NR2, etc.
[0088] In fibrous cellulose containing carbamate groups (introduced with carbamate groups), some or all of the highly polar hydroxyl groups are replaced with relatively less polar carbamate groups. Therefore, fibrous cellulose containing carbamate groups has low hydrophilicity and high affinity for low-polarity resins. As a result, fibrous cellulose containing carbamate groups exhibits excellent uniform dispersibility with resins. Furthermore, fibrous cellulose slurry containing carbamate groups has low viscosity and good handling properties.
[0089] Regarding the introduction of carbamate groups into fibrous cellulose (or cellulose raw material if carbamateization is performed before defibration), as mentioned above, there are two methods: one in which the cellulose raw material is carbamateized first and then refined, and another in which the cellulose raw material is refined first and then carbamateized. The order of refinement (e.g., defibration) and carbamateization is not limited. However, it is preferable to perform carbamateization first, followed by defibration. This is because the cellulose raw material has high dehydration efficiency before defibration, and the heating associated with carbamateization makes the cellulose raw material more easily defibrated.
[0090] Fibrous cellulose is dispersed in an aqueous medium to form a dispersion (slurry) as needed. While it is particularly preferable that the aqueous medium is entirely water, an aqueous medium containing a portion of another liquid that is compatible with water can also be used. Other liquids that can be used include lower alcohols with 3 or fewer carbon atoms.
[0091] The solid content concentration of the slurry is preferably 2 to 10% by mass, more preferably 3 to 8% by mass. If the solid content concentration is less than 2% by mass, excessive energy may be required during dehydration and drying. On the other hand, if the solid content concentration exceeds 10% by mass, the fluidity of the slurry itself decreases, and uniform mixing may not be possible even when using a dispersant. In this regard, for example, if the fineness ratio exceeds 35%, the upper limit for slurry solid content concentration from the standpoint of ensuring fluidity is 4.0% by mass. In contrast, if the fineness ratio is 35% or less, the upper limit is 10% (preferably 6.0% by mass), as described above. Therefore, if the fineness ratio is 35% or less and the slurry solid content concentration is 10% by mass or less, it is possible to reduce the amount of aqueous medium that needs to be removed from the slurry, and the solid content concentration can be increased, which has advantages such as reducing costs.
[0092] (Acid-modified resin) When fibrous cellulose is impregnated with an acid-modified resin, the acid groups ionically bond with some or all of the carbamate groups, as described above. This ionic bonding improves the reinforcing effect of the resin.
[0093] Examples of acid-modified resins that can be used include acid-modified polyolefin resins, acid-modified epoxy resins, and acid-modified styrene-based elastomer resins. However, it is preferable to use acid-modified polyolefin resins. Acid-modified polyolefin resins are copolymers of an unsaturated carboxylic acid component and a polyolefin component.
[0094] As the polyolefin component, one or more polymers of alkenes such as ethylene, propylene, butadiene, and isoprene can be selected and used. However, it is preferable to use polypropylene resin, which is a polymer of propylene.
[0095] As the unsaturated carboxylic acid component, one or more can be selected from, for example, maleic anhydrides, phthalic anhydrides, itaconic anhydrides, citraconic anhydrides, citric anhydrides, etc. However, maleic anhydrides are preferably used. In other words, it is preferable to use maleic anhydride-modified polypropylene resin.
[0096] The amount of acid-modified resin to be mixed is preferably 0.1 to 1,000 parts by mass, more preferably 1 to 500 parts by mass, and particularly preferably 10 to 200 parts by mass, per 100 parts by mass of fibrous cellulose. In particular, when the acid-modified resin is maleic anhydride-modified polypropylene resin, the amount is preferably 1 to 200 parts by mass, and more preferably 10 to 100 parts by mass. If the amount of acid-modified resin mixed is less than 0.1 parts by mass, the improvement in strength is insufficient. On the other hand, if the amount of resin mixed exceeds 1,000 parts by mass, it becomes excessive and tends to decrease the strength.
[0097] The weight-average molecular weight of maleic anhydride-modified polypropylene is, for example, 1,000 to 100,000, preferably 3,000 to 50,000.
[0098] Furthermore, the acid value of maleic anhydride-modified polypropylene (titrated with potassium hydroxide in accordance with JIS-K2501) is preferably 0.5 mg KOH / g or more and 100 mg KOH / g or less, and more preferably 1 mg KOH / g or more and 50 mg KOH / g or less.
[0099] Furthermore, the MFR (melt flow rate) of the acid-modified resin is preferably 2000 g / 10 min or less (measured under conditions of 190°C / 2.16 kg in accordance with JIS-K7210), more preferably 1500 g / 10 min or less, and particularly preferably 500 g / 10 min. If the MFR exceeds 2000 g / 10 min, the dispersibility of the fibrous cellulose may decrease.
[0100] (Dispersant) Cellulose raw materials or fibrous cellulose can be mixed with a dispersant. Preferred dispersants are compounds having an amine group and / or a hydroxyl group in aromatic compounds, and compounds having an amine group and / or a hydroxyl group in aliphatic compounds.
[0101] Dispersants inhibit hydrogen bonding between fibrous cellulose fibers. Therefore, during the kneading of fibrous cellulose and resin, the fibrous cellulose is reliably dispersed within the resin. Furthermore, dispersants also play a role in improving the compatibility between fibrous cellulose and resin. In this respect, the dispersibility of fibrous cellulose within the resin is improved.
[0102] While it is possible to add a phase solvent (chemical) separately during the kneading of fibrous cellulose and resin, mixing the fibrous cellulose and dispersant (chemical) beforehand results in more uniform adhesion of the chemical to the fibrous cellulose, thereby improving compatibility with the resin.
[0103] For example, the mixing of fibrous cellulose and resin is carried out at a temperature above the melting point of the resin. However, if the resin is polypropylene, for example, its melting point is 160°C, and therefore the mixing of fibrous cellulose and resin is carried out at around 180°C. However, if a dispersant (liquid) is added at this high temperature, it will dry out instantly. Therefore, one method involves using a resin with a low melting point to create a masterbatch (a composite resin with a high concentration of cellulose fibers), and then lowering the concentration with a regular resin. However, resins with low melting points generally have low strength. Consequently, this method may reduce the strength of the composite resin.
[0104] The amount of dispersant to be mixed is preferably 0.1 to 1,000 parts by mass, more preferably 1 to 500 parts by mass, and particularly preferably 10 to 200 parts by mass, per 100 parts by mass of fibrous cellulose. If the amount of dispersant mixed is less than 0.1 parts by mass, the improvement in resin strength may not be sufficient. On the other hand, if the amount of dispersant mixed exceeds 1,000 parts by mass, it becomes excessive and tends to decrease the resin strength.
[0105] The aforementioned acid-modified resin improves compatibility through ionic bonding between the acid groups and the carbamate groups of fibrous cellulose, thereby enhancing its reinforcing effect. Its large molecular weight makes it easily compatible with resins, which is thought to contribute to improved strength. On the other hand, the above-mentioned dispersant intervenes between the hydroxyl groups of fibrous cellulose to prevent aggregation, thereby improving dispersibility in the resin. Furthermore, because its molecular weight is smaller than that of the acid-modified resin, it can enter the narrow spaces between fibrous cellulose where the acid-modified resin cannot penetrate, thus improving dispersibility and enhancing strength. From this perspective, the molecular weight of the acid-modified resin is preferably 2 to 2,000 times, more preferably 5 to 1,000 times, the molecular weight of the dispersant.
[0106] To explain in more detail, resin powder (or granules) physically interposes itself between fibrous cellulose fibers, inhibiting hydrogen bonding and thereby improving the dispersibility of the fibrous cellulose. In contrast, acid-modified resin improves compatibility by ionic bonding between the acid groups and the carbamate groups of the fibrous cellulose, thereby enhancing the reinforcing effect. In this respect, both dispersants inhibit hydrogen bonding between fibrous cellulose fibers, but because resin powder is on the micro-order, it physically intervenes and suppresses hydrogen bonding. Therefore, although its dispersibility is lower than that of dispersants, the resin powder itself melts and forms a matrix, so it does not contribute to a decrease in physical properties. On the other hand, dispersants are at the molecular level and are extremely small, so they effectively inhibit hydrogen bonding by covering the fibrous cellulose and improving the dispersibility of the fibrous cellulose. However, they may remain in the resin and contribute to a decrease in physical properties.
[0107] (Example of manufacturing method) A mixture of fibrous cellulose, acid-modified resin, and dispersant can be dried and pulverized into a powder before being kneaded with the resin. This form eliminates the need to dry the fibrous cellulose separately before kneading with the resin, resulting in better thermal efficiency. Furthermore, if a dispersant is mixed into the mixture, there is a low risk that the fibrous cellulose (e.g., microfiber cellulose) will not redisperse even after the mixture is dried.
[0108] The mixture may be dehydrated before drying, if necessary. This dehydration can be carried out by selecting one or more types of dehydration equipment from among, for example, a belt press, screw press, filter press, twin roll, twin wire former, valveless filter, center disc filter, membrane processing, and centrifuge. As already explained, a screw press is particularly preferred from the viewpoint of dewatering efficiency and economics.
[0109] The drying of the mixture can be carried out by selecting one or more of the following methods: rotary kiln drying, disc drying, airflow drying, fluidized bed drying, spray drying, drum drying, screw conveyor drying, paddle drying, single-screw kneading drying, multi-screw kneading drying, vacuum drying, agitation drying, etc. In terms of drying efficiency and operational stability, indirect heating rotary dryers (e.g., steam tube dryers: STD) are particularly suitable.
[0110] For example, a mixture (dried material) with a dry content of 10% or less, typically around 3-7%, can be ground into a powder if necessary. Grinding of the dried material can be done by selecting one or more types of mills from, for example, a bead mill, kneader, disper, twist mill, cut mill, hammer mill, etc.
[0111] The average particle size of the powder is preferably 1 to 10,000 μm, more preferably 10 to 5,000 μm, and particularly preferably 100 to 1,000 μm. If the average particle size of the powder exceeds 10,000 μm, it may result in poor kneadability with the resin. On the other hand, reducing the average particle size of the powder to less than 1 μm requires a large amount of energy, making it uneconomical. The average particle size of powdered materials can be controlled not only by controlling the degree of grinding, but also by classification using classification devices such as filters and cyclones.
[0112] The bulk density of the mixture (powder) is preferably 0.03 to 1.0, more preferably 0.04 to 0.9, and particularly preferably 0.05 to 0.8. If the bulk density exceeds 1.0, the hydrogen bonds between the fibrous celluloses become stronger, and dispersion in the resin tends to become more difficult. On the other hand, a bulk density below 0.03 is disadvantageous in terms of transportation costs. The bulk density can be obtained by measuring it in accordance with JIS K7365.
[0113] The moisture content of the mixture (powder) supplied to the melt-kneading extruder is preferably 50% or less, more preferably 30% or less, and particularly preferably 10% or less. If the moisture content exceeds 50%, the energy required for kneading with the resin becomes enormous, making it uneconomical. The moisture content was calculated using the following formula, after drying the sample in a constant-temperature dryer, holding it at 105°C for 6 hours or more and taking the mass at which no further mass fluctuation was observed. Fiber moisture content (%) = [(Mass before drying - Mass after drying) ÷ Mass before drying] × 100 In contrast, the solid content concentration is as follows: Solid content concentration (%) = (mass after drying ÷ mass before drying) × 100 (= 100 - fiber moisture content)
[0114] (Resin mixing process) As shown in the embodiment in Figure 1, it is preferable to incorporate powdered resin by a "resin mixing process" prior to dehydration and drying. If this is referred to as pre-resin, the presence of this pre-resin inhibits hydrogen bonding between dehydrated and dried microfiber cellulose, thereby improving dispersibility in the pre-resin during kneading. Furthermore, the presence of a water-free pre-resin during the dewatering process allows for more efficient dewatering of the fibers. On the other hand, by adding (including) the pre-resin after the dewatering process or after the drying process, material loss of resin components that would otherwise be lost as filtrate during the dewatering process can be reduced.
[0115] The pre-resin used here may be the same type as the resin mixed with the fibrous cellulose (the resin used as the main raw material) or a different type, but it is preferable that it be the same type. If the main raw material is, for example, polypropylene resin, the pre-resin can also be polypropylene resin.
[0116] Furthermore, the pre-resin may contain the aforementioned dispersant and / or acid-modified resin. When the acid-modified resin is, for example, a maleic anhydride-modified polypropylene resin in which propylene is the polyolefin component and maleic anhydrides are the unsaturated carboxylic acid components, it is preferably in the form of a powdered maleic anhydride-modified polypropylene resin obtained prior to dehydrating and drying the fibrous cellulose.
[0117] The fibrous cellulose-containing material obtained as described above, for example in powder form, is subjected to a dehydration step and a drying step, and then kneaded in a kneading step to obtain a fibrous cellulose composite resin. This mixing can be carried out, for example, by mixing pelletized resin with powdered fibrous cellulose-containing material, or by first melting the resin and then adding the powdered material to the molten material. Acid-modified resins and dispersants can also be added at the melt-mixing stage, but as mentioned above, it is preferable to add them prior to the dehydration and drying of the fibrous cellulose.
[0118] For the melt-mixing process, one or more types of equipment can be selected and used from, for example, single-screw or multi-screw (two or more) mixing extruders, mixing rolls, kneaders, roll mills, Banbury mixers, screw presses, dispersers, etc. While single-screw and twin-screw extruders are commonly used, twin-screw extruders offer higher productivity and greater operational flexibility compared to single-screw extruders. Therefore, twin-screw extruders are preferred for the production of composite resin composition pellets in the embodiments of the present invention. Two or more twin-screw compounding extruders may be used in parallel or in series.
[0119] The mixing temperature is above the glass transition temperature of the resin and varies depending on the type of resin, but is preferably 80 to 280°C, more preferably 90 to 260°C, and particularly preferably 100 to 240°C.
[0120] As thermoplastic resins to be used, one or more can be selected from, for example, polyolefins such as polypropylene (PP) and polyethylene (PE), polyester resins such as aliphatic polyester resins and aromatic polyester resins, polyacrylic resins such as polystyrene, methacrylate, and acrylate, polyamide resins, polycarbonate resins, and polyacetal resins.
[0121] However, it is preferable to use at least one of polyolefin and polyester resin. Furthermore, as polyolefin, polypropylene is preferred. In addition, as polyester resin, aliphatic polyester resins such as polylactic acid and polycaprolactone can be exemplified, and aromatic polyester resins such as polyethylene terephthalate can be exemplified, but it is preferable to use a biodegradable polyester resin (also simply called "biodegradable resin").
[0122] As for biodegradable resins, one or more can be selected and used from, for example, hydroxycarboxylic acid-based aliphatic polyesters, caprolactone-based aliphatic polyesters, and dibasic acid polyesters.
[0123] As the hydroxycarboxylic acid aliphatic polyester, one or more can be selected and used from among homopolymers of hydroxycarboxylic acids such as lactic acid, malic acid, glucose acid, and 3-hydroxybutyric acid, or copolymers using at least one of these hydroxycarboxylic acids. However, it is preferable to use polylactic acid, copolymers of lactic acid and the above hydroxycarboxylic acids excluding lactic acid, polycaprolactone, or copolymers of at least one of the above hydroxycarboxylic acids and caprolactone, and it is particularly preferable to use polylactic acid.
[0124] For example, L-lactic acid or D-lactic acid can be used as the lactic acid, and these lactic acids may be used individually or two or more types may be selected and used together.
[0125] As the caprolactone-based aliphatic polyester, one or more can be selected and used from, for example, a homopolymer of polycaprolactone or a copolymer of polycaprolactone or the above-mentioned hydroxycarboxylic acid.
[0126] As the dibasic acid polyester, one or more types can be selected and used from, for example, polybutylene succinate, polyethylene succinate, and polybutylene adipate.
[0127] Biodegradable resins may be used individually or in combination of two or more types.
[0128] The resin may contain inorganic fillers, preferably in a proportion that does not hinder thermal recycling. Examples of these inorganic fillers include elemental metal elements from Groups I to VIII of the periodic table, such as Fe, Na, K, Cu, Mg, Ca, Zn, Ba, Al, Ti, and silicon, as well as oxides, hydroxides, carbon salts, sulfates, silicates, sulfites, and various clay minerals composed of these compounds.
[0129] Specifically, examples include barium sulfate, calcium sulfate, magnesium sulfate, sodium sulfate, calcium sulfite, zinc oxide, silica, heavy calcium carbonate, light calcium carbonate, aluminum borate, alumina, iron oxide, calcium titanate, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, sodium hydroxide, magnesium carbonate, calcium silicate, clay worlastonite, glass beads, glass powder, silica sand, silica, quartz powder, diatomaceous earth, white carbon, glass fiber, etc. Multiple inorganic fillers may be included. They may also be found in recycled paper pulp.
[0130] The blending ratio of fibrous cellulose and resin is preferably 1 part by mass or more of fibrous cellulose and 99 parts by mass or less of resin, more preferably 2 parts by mass or more of fibrous cellulose and 98 parts by mass or less of resin, and particularly preferably 3 parts by mass or more of fibrous cellulose and 97 parts by mass or less of resin. Further, it is preferably 50 parts by mass or less of fibrous cellulose and 50 parts by mass or more of resin, more preferably 40 parts by mass or less of fibrous cellulose and 60 parts by mass or more of resin, and particularly preferably 30 parts by mass or less of fibrous cellulose and 70 parts by mass or more of resin. In particular, when the content of fibrous cellulose is 10 to 50 parts by mass, the strength of the resin composition, particularly the flexural strength and the tensile modulus, can be significantly improved.
[0131] The content ratio of fibrous cellulose and resin contained in the finally obtained resin composition is usually the same as the above-mentioned blending ratio of fibrous cellulose and resin.
[0132] The solubility parameter (cal / cm 3 ) 1 / 2 (SP value) difference, that is, the SP of fibrous cellulose MFC value and the SP of the resin POL value, the difference in SP values can be defined as SP MFC value minus SP POL value. The difference in SP values is preferably 10 to 0.1, more preferably 8 to 0.5, and particularly preferably 5 to 1. If the difference in SP values exceeds 10, the fibrous cellulose may not disperse in the resin, and the reinforcing effect may not be obtained. On the other hand, if the difference in SP values is less than 0.1, the fibrous cellulose will dissolve in the resin, fail to function as a filler, and no reinforcing effect can be obtained. In this regard, the SP of the resin (solvent) POL value and the SP of the fibrous cellulose (solute) MFC The smaller the difference in values, the greater the reinforcing effect.
[0133] Solubility parameter (cal / cm 3 ) 1 / 2The SP value is a measure of the intermolecular forces acting between a solvent and a solute. Solubility increases as the SP values of the solvent and solute are similar.
[0134] (Molding process) The fibrous cellulose and resin extruded from the melt-mixing extruder are extruded in a strand-like manner. The extruded material can then be molded into a desired shape. The size, thickness, and shape of this molded material are not particularly limited. Similar to general-purpose resins, it can be used as a molding material in the form of sheets, pellets, powders, fibers, etc.
[0135] The temperature during the molding process is above the glass transition temperature of the resin and varies depending on the type of resin, but is, for example, 90 to 260°C, preferably 100 to 240°C. For the molding process of the molding raw materials, one or more types of machines can be selected and used from, for example, injection molding machines, blow molding machines, hollow molding machines, blow molding machines, compression molding machines, extrusion molding machines, vacuum molding machines, and pressure molding machines.
[0136] Furthermore, the strand-shaped extruded material can be spun into fibers and blended with the aforementioned plant materials to form mats or boards. The blending can be done, for example, by simultaneously depositing the materials using an air-lay system.
[0137] (Other compositions) In addition to typical microfiber cellulose, fibrous cellulose may also contain cellulose nanofibers. Cellulose nanofibers are fine fibers, similar to microfiber cellulose, and play a complementary role to microfiber cellulose in improving the strength of the resin. However, if possible, it is preferable to use only microfiber cellulose without including cellulose nanofibers as fine fibers. The average fiber diameter (average fiber width; average diameter of a single fiber) of the cellulose nanofibers is preferably 4 to 100 nm, more preferably 10 to 80 nm.
[0138] Furthermore, fibrous cellulose may contain pulp. The pulp plays a role in significantly improving the dewatering properties of the cellulose fiber slurry. However, as with cellulose nanofibers, it is most preferable not to include pulp, i.e., to have a pulp content of 0% by mass.
[0139] The composite resin composition may also contain, or may contain, fibers derived from plant materials obtained from various plants, including, in addition to fine fibers and pulp, kenaf, jute, Manila hemp, sisal, ganpi, mitsumata, kozo, banana, pineapple, coconut, corn, sugarcane, bagasse, palm, papyrus, reed, esparto, survivalgrass, wheat, rice, bamboo, various coniferous trees (such as cedar and cypress), broad-leaved trees, and cotton.
[0140] The composite resin composition may contain one or more of the following: antistatic agents, flame retardants, antibacterial agents, colorants, radical scavengers, foaming agents, etc., added within a range that does not impair the effects. These raw materials may be added to a dispersion of fibrous cellulose, added during the kneading of fibrous cellulose and resin, added to the resulting mixture, or added by other methods. However, from the standpoint of manufacturing efficiency, it is preferable to add them during the kneading of fibrous cellulose and resin.
[0141] The resin composition may contain an ethylene-α-olefin copolymer elastomer or a styrene-butadiene block copolymer as a rubber component. Examples of α-olefins include butene, isobutene, pentene, hexene, methylpentene, octene, decene, and dodecene.
[0142] The MFR (melt flow rate) of the resin composition (preferably when the fiber content is 55%) is preferably 0.01 to 20 g / 10 min, more preferably 0.02 to 10 g / 10 min, and particularly preferably 0.03 to 5 g / 10 min. If the MFR is 0.01 g / 10 min or higher, strands can be reliably drawn. However, if the MFR exceeds 1.0 g / 10 min, the molecular weight of the base resin may decrease too much, potentially making it impossible to meet the required strength properties.
[0143] (Definition, measurement method, etc.) (Average fiber diameter) The method for measuring the average fiber diameter of fine fibers (microfiber cellulose and cellulose nanofibers) is as follows: First, 100 ml of an aqueous dispersion of fine fibers with a solid content concentration of 0.01-0.1% by mass is filtered through a Teflon® membrane filter, and the solvent is replaced once with 100 ml of ethanol and three times with 20 ml of t-butanol. Next, the dispersion is freeze-dried and coated with osmium to prepare the sample. This sample is observed using an electron microscope (SEM) at a magnification of 3,000x to 30,000x depending on the width of the constituent fibers. Specifically, two diagonal lines are drawn on the observed image, and three arbitrary straight lines are drawn passing through the intersection of the diagonals. Furthermore, the width of a total of 100 fibers that intersect these three straight lines is measured visually. The median diameter of the measured values is then taken as the average fiber diameter.
[0144] (Aspect ratio) The aspect ratio is the value obtained by dividing the average fiber length by the average fiber width. A larger aspect ratio increases the number of points where snagging occurs, thus increasing the reinforcement effect. On the other hand, it is thought that the ductility of the resin decreases as more snagging occurs. [Industrial applicability]
[0145] The fibrous cellulose composite resin obtained by the present invention can be used as interior, exterior, and structural materials for transportation equipment such as automobiles, trains, ships, and airplanes; as casings, structural materials, and internal components for electrical appliances such as personal computers, televisions, telephones, and watches; as casings, structural materials, and internal components for mobile communication equipment such as mobile phones; as casings, structural materials, and internal components for portable music players, video players, printing machines, photocopiers, sporting goods, office equipment, toys, and sporting goods; as interior, exterior, and structural materials for buildings and furniture; as office equipment such as stationery; and for other applications such as packaging, trays, protective components, and partition components.
Claims
1. A dehydration step is performed in which an aqueous dispersion containing fibrous cellulose at a solid content concentration of 2 to 10% by mass is dehydrated to a solid content concentration of 20 to 80% by mass using a filter press or screw press. A drying process in which the dehydrated material is dried to a moisture content of 10% or less using an indirect heating type steam tube dryer, A composite resin formation process involves kneading the dried material after a drying process to obtain a composite resin, The process includes a resin-containing step in which a resin is added prior to the composite resin formation step. A method for producing a composite resin of fibrous cellulose, characterized by the above.
2. A method for producing a composite resin of fibrous cellulose according to claim 1, further comprising a crushing step of crushing the dehydrated material between the dehydration step and the drying step.
3. A method for producing a composite resin of fibrous cellulose according to claim 1 or 2, comprising a maleic anhydride-modified polypropylene mixing step of mixing maleic anhydride-modified polypropylene with the fibrous cellulose before supplying the aqueous dispersion of the fibrous cellulose to the filter press or screw press.
4. The method for producing a composite resin of fibrous cellulose according to claim 1, wherein the composite resin formation step involves kneading the dried product, which has been dried through the drying step, to obtain a composite resin.
5. A method for producing a composite resin of fibrous cellulose according to claim 4, further comprising a productization step of extruding the composite resin obtained by kneading in the composite resin formation step as strands, cutting the extruded material in units of length, and dewatering the cut pieces to obtain a composite resin in the form of pellets.
Citation Information
Patent Citations
Solid powder cosmetic
JP2024107247A
Fibrous cellulose-containing material, fibrous cellulose composite resin, and method for producing fibrous cellulose-containing material
JP7557494B2